National complicated acute diverticulitis (CADS) study: a protocol for a prospective observational scoping study for acute diverticulitis. Issue 1 (1st January 2016) - Shaikh, Shafaque
Abstract : Background: Diverticular disease is a widely prevalent disease in western society, and acute diverticulitis is a common acute surgical presentation. However, there is a lack of level 1 evidence addressing the multifaceted presentations associated with acute diverticulitis. There is also a lack of robust epidemiological data that could be used to meaningfully inform randomised controlled trials. The National CADS project aims to generate baseline data for a cohort of patients managed for clinically suspected acute diverticulitis and evaluate the impact of variability in the management approach on patient outcomes in the short (3 months) and long (2 years) term. Method: A Unit policy questionnaire will be completed by the principal investigator from all participating centres prior to study initiation. All patients aged above 18 years admitted with clinical suspicion of acute diverticulitis will be included from UK hospitals providing acute surgical care. Demographic, clinical, inpatient stay and outpatient follow-up data will be collected for index admissions between July and September 2014, 3 months follow-up and finally a 2-year follow-up. Results: The study attracted participation from 108 centres nationally and has so far generated data on 2500 patients admitted between 1 July 2014 and 30 September 2014. Short-term follow-up data have been obtained for this cohort. Conclusions: The National CADS study is currently ongoing with the long-term outcomes data anticipated to be submitted in autumn of 2016.